Protecting Abortion Access: The Experiences of Clinic Volunteers From Roe to Dobbs - Crookston, Shara (Lexington Books, 2023)
In a post Roe society where abortion is becoming increasingly difficult to access, abortion clinic escorts ensure patient safety and comfort. This qualitative study highlights the challenges and motivations escorts experienced at clinics across the country both pre and post Dobbs. Drawing on interviews with clinic escorts, the author examines how increasing abortion restrictions, lack of police support, massive clinic closures, and upticks in anti-abortion protesting from Christian organizations impact the clinic escorts’ work and their perceived ability to keep the sidewalks of their clinics peaceful for patients seeking abortion care.